The effect of voluntary participation on cooperation - Nosenzo, Daniele; Tufano, Fabio (Elsevier, 2017)
We study the effects of voluntary participation on cooperation in collective action problems. Voluntary participation may foster cooperation through a mechanism of assortative selection of interaction partners based on false consensus bias, or through a mechanism whereby the decision to not participate can be used as a threat against free-riders. We examine the effectiveness of these mechanisms in a one-shot public goods experiment. Voluntary participation has a positive effect on provision only through the threat of non-participation. Assortative selection of interaction partners seems to play a minor role in our setting, whereas the threat of non-participation is a powerful force to discipline free-riding.